Long-Term Isolation Elicits Depression and Anxiety-Related Behaviors by Reducing Oxytocin-Induced GABAergic Transmission in Central Amygdala - Han, Rafael T.; Kim, Young-Beom; Park, Eui-Ho; Kim, Jin Yong; Ryu, Changhyeon; Kim, Hye Y.; Lee, JaeHee; Pahk, Kisoo; Shanyu, Cui; Kim, Hyun; Back, Seung K.; Kim, Hee J.; et al. (Frontiers in Molecular Neuroscience, 2018)
Isolation stress is a major risk factor for neuropsychiatric disorders such as depressive and anxiety disorders. However, the molecular mechanisms underlying isolation-induced neuropsychiatric disorders remain elusive. In the present study, we investigated the subcellular mechanisms by which long-term isolation elicits depression and anxiety-related behaviors in mice. First, we found that long-term isolation induced depression-related behaviors in the forced swimming test (FST) and the sucrose preference test, as well as anxiety-related behaviors in the elevated zero maze test (EZMT) and the open field test. Next, we showed that intra-central amygdala (CeA) injection of oxytocin (OXT), but not intracerebroventricular injection, attenuated isolation-induced depression and anxiety-related behaviors via oxytocin receptor (OXTR), not vasopressin-1a receptor (V1aR), in the FST and EZMT, respectively. Quantitative real-time PCR analysis revealed that after 5 weeks of isolation, mRNA transcription of OXTR in the CeA, but not that of V1aR, significantly decreased, whereas OXT and vasopressin mRNA transcription in the PVN did not change significantly. Whole-cell patch clamping of acute brain slices demonstrated that the frequency of miniature inhibitory postsynaptic currents (mIPSCs) in CeA neurons, but not their amplitude, was lower in isolated mice than in group-housed mice. Notably, OXT treatment increased the mIPSC frequency in the CeA neurons, but to lesser extent in the case of isolated mice in group-housed mice via OXTR. Taken together, our findings suggest that long-term isolation down-regulated OXTR mRNA transcription and diminished OXT-induced inhibitory synaptic transmission in the CeA, which may contribute to the development of depression and anxiety-related behaviors in isolated mice through the enhancement of CeA activity.